Prevalence, potential virulence genes, and antimicrobial resistance of Aeromonas spp. in farm-raised Oreochromis niloticus and Labeo rohita in Noakhali, Bangladesh - Noimul Hasan Siddiquee; Imam Hossain; Popy Devnath; Farzana Islam; Rahima Akter; Mridul Gope Topu; Israt Jahan Mitu; Md Abdul Hannan; Md. Shariful Islam; Mohammad Sharif Uddin; Sutapa Bhowmik (PLoS ONE, 2026)
Background Aeromonas species are ubiquitous aquatic bacteria and opportunistic pathogens associated with motile Aeromonas septicemia (MAS) in freshwater fish. MAS is characterized by hemorrhagic lesions and septicemia and can cause severe economic losses in aquaculture. The increasing occurrence of antimicrobial-resistant Aeromonas strains has raised concerns for fish health, aquaculture sustainability, and public health. Aim This study aimed to determine the prevalence, species distribution, virulence gene profiles, and antimicrobial resistance patterns of Aeromonas spp. isolated from farm-raised Oreochromis niloticus and Labeo rohita collected from local markets in Noakhali, Bangladesh. Methods A total of 22 Aeromonas isolates were obtained from intestinal samples and characterized using biochemical assays and PCR amplification of the gyrB gene. Species-level identification and phylogenetic relationships were determined by 16S rRNA gene sequencing. Antimicrobial susceptibility was evaluated using the disc diffusion method following CLSI guidelines, and multiple antibiotic resistance (MAR) was calculated for each isolate. PCR-based screening of nine virulence-associated genes was performed to assess pathogenic potential. Results Phylogenetic analysis identified five Aeromonas species, with A. veronii as the predominant species. Several virulence genes, particularly act , alt , and ast , were frequently detected among the isolates. High levels of antimicrobial resistance were observed against β-lactam antibiotics, and MAR index analysis indicated that many isolates were multidrug resistant. Conclusion These findings highlight the presence of virulence gene and multidrug-resistant Aeromonas in farm-raised fish in Bangladesh. Continuous surveillance and responsible antimicrobial use are essential to mitigate potential risks to aquaculture and public health.